2011
DOI: 10.2298/abs1103785j
|View full text |Cite
|
Sign up to set email alerts
|

Ecological investigation of zooplankton abundance in the river Haraz, northeast Iran: Impact of environmental variables

Abstract: The influence of physicochemical properties of Haraz river on its zooplankton composition and abundance were investigated at three sites for one year between August 2009 and July 2010. The present study records for the first time the aspects of zooplankton diversity and composition in relation to the physicochemical environment of the Haraz river. Only three groups of zooplankton were found: Rotifera with eighteen genera; Cladocera with nine and Copepoda with six genera. Rotifera was the predominant grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
2
15
0
1
Order By: Relevance
“…The high values of hardness recorded amid winter season in the Baldi stream may be ascribed to the increased mobilization of hardness causing components like calcium and magnesium to be discharged from the subsurface ground waters having higher hardness (USEPA 2000;Badrakh et al 2008;Sharma et al 2016). Higher values of hardness were also reported in Haraz River, Iran (Jafari et al 2011). The concentration of calcium ranged from 68.33 mg L −1 (S1) to 60.35 mg L −1 (S3) in the Baldi stream (Sharma et al 2016).…”
Section: Cations and Anionsmentioning
confidence: 92%
“…The high values of hardness recorded amid winter season in the Baldi stream may be ascribed to the increased mobilization of hardness causing components like calcium and magnesium to be discharged from the subsurface ground waters having higher hardness (USEPA 2000;Badrakh et al 2008;Sharma et al 2016). Higher values of hardness were also reported in Haraz River, Iran (Jafari et al 2011). The concentration of calcium ranged from 68.33 mg L −1 (S1) to 60.35 mg L −1 (S3) in the Baldi stream (Sharma et al 2016).…”
Section: Cations and Anionsmentioning
confidence: 92%
“…Hoffman (1977) suggested that temperature and oxygen are the main but not the only determinative factors influencing rotifer abundance distribution as confirmed by not significant correlation found between rotifer species and these parameters, with the only exception of Tricotria pocillum, positively related to temperature. Alkaline pH was also found to favor zooplankton development in the river (Jafari et al, 2011), but our analysis revealed an inverse relationship between pH and some rotifer species, such as those belonging to Cephalodella, Euchlanis and Lepadella genera. Some species of these genera were found occurring with high abundances at pH values lower than 7 (Bērzin¸sˇand Pejler, 1987).…”
Section: Discussionmentioning
confidence: 58%
“…In the present study, physical factor best explaining zooplankton abundance spatial pattern was conductivity alone or in association with temperature and dissolved oxygen. Conductivity was found to enhance zooplankton growth and abundance (Hujare, 2005;Jafari et al, 2011), as demonstrated by the high correlation coefficients resulted for some rotifer species. Hoffman (1977) suggested that temperature and oxygen are the main but not the only determinative factors influencing rotifer abundance distribution as confirmed by not significant correlation found between rotifer species and these parameters, with the only exception of Tricotria pocillum, positively related to temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, species variation, distribution and abundance of zooplankton highly depend on the chemical and physical properties of water (Patra et al 2011). The species diversity index is a relevant tool for water quality assessment and a basis for biomonitoring by evaluating the structural complexity of zooplankton assemblages (Jafari et al 2011;Patra et al 2011). In the present study, the Shannon-Wiener index (H 0 ) for copepods was fairly low: H 0 was ,1.5 bits individual À1 for 55% of stations, including most northern stations (S1-10), except S3, S5 and S10, which had pioneer communities at the colonisation stage, and ranging between 1.5 and 2.5 bits individual À1 for the other stations, demonstrating a transition ecosystem at the diversification stage (Shannon and Weaver 1963).…”
Section: Discussionmentioning
confidence: 99%